Предмет: Алгебра,
автор: Ivanius02
Подайте в виде многочлена
(х+9)²
(3a-8b)²
(m-7)(m+7)
(6a+10b)(10b-6a)
Ответы
Автор ответа:
0
(х+9)^2 = х^2 + 18х + 81
(3a - 8b)^2 = 9a^2 - 48ab + 64b^2
(m - 7)(m + 7) = m^2 - 49
(6a + 10b)(6a - 10b) = 36a^2 - 100b^2
(3a - 8b)^2 = 9a^2 - 48ab + 64b^2
(m - 7)(m + 7) = m^2 - 49
(6a + 10b)(6a - 10b) = 36a^2 - 100b^2
Похожие вопросы
Предмет: История,
автор: step2ash2ka8
Предмет: Алгебра,
автор: stangennan
Предмет: Алгебра,
автор: rman265656
Предмет: Математика,
автор: нигораахмедова